Cell Plasticity in Lung Injury and Repair: Report from an NHLBI Workshop, April 19–20, 2010 - Borok, Zea (American Thoracic Society, 2011)
In April 2010, a NIH workshop was convened to discuss the current state of understanding of lung cell plasticity, including the responses of epithelial cells to injury, with the objectives of summarizing what is known, what the field needs to know, and how to get there. The proximal stimulus for this workshop is the body of recent evidence suggesting that plasticity is a prominent but incompletely characterized property of lung epithelial cells, and that a focus on understanding this aspect of epithelial cell biology in particular, may be an important window into disease pathobiology and pathogenesis. In addition to their many vital functions in maintaining tissue homeostasis, epithelial cells have emerged as both a central target of disease initiation and an active contributor to disease progression, making a workshop to investigate the role of cell plasticity in lung injury and repair timely. The workshop was organized around four major themes: lung epithelial cell plasticity, signaling control of plasticity, fibroblast plasticity and crosstalk, and translation to human disease. Although this breakdown was recognized to be somewhat artificial, it was felt that this approach would promote cross-fertilization among groups that ordinarily do not communicate and lend itself to the generation of new approaches. The summary reports of individual group discussions below are followed by consensus priorities and recommendations of the workshop participants.